Will Multidisciplinary Collaboration Reduce the Disability Rate of Diabetic Foot (2009–2019)?—A Study Based on the Perspective of Organizational Reform - Hou, Mengchi; Gong, Xue; Chang, Wenhu; Dong, Jie; Zhao, Feifei; Ji, Zhili; Guo, Rui (Frontiers in Public Health, 2021)
Objectives Discuss the experience and practice of multidisciplinary cooperation of diabetic foot in China and analyze its impact on the quality of care. Methods This study observed the medical procedure by interviewing twelve key personnel in-depth. We extracted data from medical records and assessed the effect of MDT in three dimensions: quality, efficiency, and cost, to eventually achieve a final conclusion. Results The studied reform includes the following three aspects: the adjustment of hospital buildings layout and disciplines, one-stop outpatient, and one-stop inpatient service. After the multidisciplinary collaboration, the rate of above-knee amputation is reduced by 3.63%, the disability score per 100 diabetic foot patients decreases by 6.12, the average length of stay decreases significantly, and the cost of hospitalization shows an increasing trend. Conclusions Multidisciplinary collaboration is performed based on spatial layout adjustment and clinical pathway optimization, which provide more comprehensive and integrated care than a general medical team or a single specialist, thereby reducing the rate of disability, shortening the length of hospitalization. Besides, the new measurable indicator called disability score per 100 diabetic foot patients has been verified to evaluate the living ability of patients after surgery. This paper provides a reference for organizational reform of multidisciplinary diseases to support treatment and management of other multiorgan diseases.